An appraisal of erosion and runoff conditions in various agro-ecologies - ADAK, TARUN; BABU, NARESH (Journal of Soil and Water Conservation, 2025)
Quantification of soil erosion from food production agro-ecologies is very important for developing advanced strategies and policy planning to meet the control measures. Runoff losses during the rainy season from orchards, crop fields, steep lands, watersheds, forests etc. have enormous contribution to nutrient loss and tremendously affect the productivity scenarios. Climatic conditions influence on the intensity of rainfall and also had impacts on various orchards, cereals, pulses, oilseeds, plantations, spices, medicinal plants and thus quality produce via water erosion in different agro-ecologies. Trees plantation, turmeric in interspaces, vegetation cover, vegetation barriers and inclusion of drumstick with leguminous hedgerows effectively enhanced conservation potential and productivity. Scientific efforts were made to enhance conservation vis-à-vis production. Management of resource conservation was thus given top priority in food production system. Hence, scientific approaches to appraise the erosion (both soil and water) were thus felt urgent for economic contribution towards financial sectors.